Avaliação ultrassonográfica de medidas temporais do deslocamento do osso hioide durante a deglutição após tireoidectomia - Costa, Bianca Oliveira Ismael da (2019)
Introduction: Thyroidectomy could affect the displacement time of the hyoid bone (HB) during swallowing, which can be investigated by quantitative ultrasound assessment. Objective: 1) To verify the applicability of Transcutaneous Laryngeal Ultrasonography (TLUSG) in laryngeal assessment after thyroidectomy; 2) To compare the sonographic measurements of HB displacement time during swallowing between thyroidectomy patients and healthy volunteers; and to relate these measurements with age, clinical characteristics and self-reported swallowing and voice outcomes. Method: The first article is an integrative review of the literature that followed the methodological procedures for this type of study. The second article is a cross-sectional study with comparative groups, with 20 thyroidectomy female patients (EG) and 20 non-thyroidectomy female volunteers (CG). All performed the USGLT during a swallow of 10 milliliters of liquid and honey-thick viscosity, offered in a spoon. The exams were recorded in video (30 frames/second) and six temporal measures were extracted and analyzed according to a standardized protocol. The non-parametric Mann-Whitney test and the Spearman correlation test, both with a 95% confidence interval, were performed. Results: Article 1) TLUSG helps investigate vocal fold mobility after thyroidectomy, but is rarely used in swallowing studies; Article 2), the elevation and maximum displacement times of the HB were significantly lower in the EG compared to the CG in the swallowing of the honey-thick viscosity. No other variables were related to or correlated with ultrasound measurements. Conclusion: 1) USGLT helps investigate vocal fold mobility after thyroidectomy, but is rarely used in swallowing studies; 2) female thyroidectomy patients have a shorter time of elevation and maximum displacement of HB during swallowing compared to those who did not undergo surgery. There is no difference between temporal ultrasound measurements in relation to age, clinical characteristics and complaints of swallowing and voice in women undergoing thyroidectomy.